Bleeding with Apixaban and Dalteparin in Patients with Cancer-Associated Venous Thromboembolism: Results from the Caravaggio Study - Ageno, Walter; Vedovati, Maria Cristina; Cohen, Ander; Huisman, Menno; Bauersachs, Rupert; Gussoni, Gualberto; Becattini, Cecilia; Agnelli, Giancarlo (Thrombosis and Haemostasis, 2020)
Background Direct oral anticoagulants are recommended for the treatment of cancer-associated thrombosis (CAT) as an alternative to low-molecular-weight heparin (LMWH), but an increased bleeding risk in patients with gastrointestinal cancer was reported. The Caravaggio study compared apixaban and dalteparin for the treatment of patients with CAT. Here we describe sites of bleeding, associated cancer sites, clinical presentation, and course of major bleeding in patients included in the Caravaggio study.Methods The Caravaggio study was a multinational, randomized, open-label, noninferiority study. Bleeding events and the severity of major bleedings were adjudicated by a committee unaware of treatment allocation using predefined criteria; for the purpose of this analysis, data were analyzed in the safety population.Results Major bleeding occurred in 22 of 576 patients on apixaban (3.8%) and in 23 of 579 patients on dalteparin (4.0%). The sites of major bleeding and their distribution according to the type of cancer were similar between the two treatment groups. Major bleeding occurred in nine patients with gastrointestinal cancer in each treatment group. The clinical presentation of major bleeding was severe or fatal in 6 patients on apixaban and in 5 patients on dalteparin, while the clinical course was severe in 5 patients on apixaban and in 7 patients on dalteparin.Conclusion Apixaban is a safe alternative to LMWH for the treatment in patients with CAT. No excess in gastrointestinal bleeding was observed in patients who received apixaban, including those with gastrointestinal cancer.
Keywords: anticoagulant; bleeding; cancer; treatment; venous thromboembolism